Pengaruh Penambahan Bahan Organik dalam Pembuatan Pupuk Organik Padat Sludge Biogas Feses Sapi Perah terhadap Kandungan N, P dan K - E Febriyanti; E Purwati; Apriman Apriman (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
This research aims to test the hypothesis that a combination of solid Sludge biogas from manure of dairy cows with a different ratio of water and the addition of quality-enhancing organic material can increase the content of N, P and K. This research method using a randomized block design (RBD) with 3 x 4 factorial design with two replicates. Factor A is the solid Sludge and dairy manure biogas, Factor B is the quality-enhancing organic material (blood meal, bone meal, rice husk ash and mixed). Variables observed included N-organic content, PO4 and K2O. The results showed solid Sludge composting dairy manure biogas with different ratio of water and adding blood meal increased the organic content of the N-1.6135%, faecal Sludge dairy cows with a different ratio of water and the addition of bone meal to improve the content of 2.9089% PO4 dairy manure and Sludge with different ratio of water and the addition of a mixture of organic materials (1% blood meal, bone meal ash 3% and 3%) increase the content of 0.4382% K2O.